Pengaruh Gaya Kepemimpinan Kepala Sekolah, Profesionalisme Guru, dan Lingkungan Kerja Terhadap Kinerja Guru Mi Muslimat Nu Pucang Sidoarjo - Muhammad Bashor; Didit Darmawan (Departement of Mathematics Education, 2024)
This research aims to investigate the influence of the principal's leadership style and teacher professionalism on teacher performance at MI Muslimat NU Pucang Sidoarjo, with the main focus on improving the quality of education. In facing demands for improving the quality of education, serious attention to key factors such as the leadership style of school principals and the level of teacher professionalism needs to be researched. Through regression analysis, this research provides evidence that the principal's leadership style and the level of teacher professionalism have a significant contribution to teacher performance. An effective leadership style, which includes the principal's ability to provide direction, motivate and create a positive work environment, is considered a crucial element in establishing a quality learning process. Meanwhile, the level of teacher professionalism, which involves commitment to self-development, work ethics, and the ability to integrate the latest knowledge in learning, is also considered important for improving the quality of education. These findings strengthen the understanding that effective leadership and teacher professionalism have a positive impact in achieving the goal of improving the quality of education. Given the complex relationships between these variables, this research provides valuable insights for education stakeholders, especially in designing strategies and policies that support teacher professional growth and well-being.